HUMANISTIC SCHOOL MANAGEMENT FOR SAFE AND SUPPORTIVE SCHOOL CULTURES: AN INTEGRATIVE FRAMEWORK - Paul Arjanto; Sarlota Singerin; Bety Diana Serly Hetharion; Vando Kristi Makaruku (EDUCATIONE, 2026)
Policies that define safe schools often specify desired conditions but leave unclear how leaders can convert rights-based commitments into routines that shape everyday experience. This study develops an integrative framework for humanistic school management within Indonesia's Budaya Sekolah Aman dan Nyaman (BSAN), rendered here as Safe and Supportive School Culture. An integrative policy-conceptual review synthesized 40 substantive sources published between 1943 and 2026 across humanistic management, school climate, leadership, relational pedagogy, inclusion, partnership, restorative practice, digital safety, and authoritative policy standards. Sources were analyzed through deductive coding against four BSAN protection domains and inductive mechanism coding, followed by model construction and contradiction checking. The synthesis identifies five mutually reinforcing organizational capabilities: dignity-anchored leadership, protective governance, relational pedagogy, collaborative partnership, and continuous evaluation. These capabilities operate through relational trust, procedural predictability, psychological safety, stakeholder legitimacy, and organizational learning. The framework distinguishes harm reduction from flourishing and shows that humanism requires enforceable systems, not benevolent interpersonal style alone. It also surfaces five implementation tensions: care versus permissiveness, early detection versus surveillance, participation versus tokenism, contextual adaptation versus rights dilution, and restorative responses versus mandatory referral. The study contributes a multilevel architecture, implementation roadmap, and balanced indicator set linking policy mandates to observable practice. Empirical multi-site testing should examine whether the proposed mechanisms predict safety, belonging, engagement, and equitable well-being across diverse school contexts.